EFFECT OF STOCK’S ALTERNATIVE ASSETS ON THE STOCK MARKET IN IRAQ (World Economics and Finance Bulletin, 2024)
The stock exchange is one of the components of the financial market and one of the most important institutions of the capital market, which plays an important role in equipping savings resources in investments and the financial needs of production units. Given that investment is one of the necessities in the process of economic growth of any country and is one of the important factors of development in this century. It can be concluded that the stock exchange is a part of the economy that is related to other sectors of the economy and can play an important role in the economic growth and development of a country. The stock price index and its return have always been affected by economic variables and the recession and stock market boom are also strongly affected by the fluctuations of these variables, so in this study, we will examine this issue.